The Science of Sustainability Approach in Halal Tourism Development Based on the Useful Power of the Malay Community in Palembang - Muhammad Amiin Fauzi; Ris'an Rusli; Heri Junaidi; Hilda (Jurnal Penelitian Pendidikan IPA, 2026)
This research investigates the construction of halal tourism development grounded in the sustainability science approach, specifically leveraging the useful power (daya guna) of the Malay community in Palembang, Indonesia. While halal tourism has grown globally, existing models often prioritize commercial metrics over substantive religious values and local cultural wisdom. This study employs a qualitative phenomenological approach to analyze how the Malay community constructs the meaning of "halal" within their socio-cultural context. The results indicate that sustainable halal tourism requires integrating Islamic principles with local Malay identity, encapsulated in the philosophy "Sondok Piyogo: Adat Dipangku, Syariat Dijunjung." A conceptual model is proposed wherein community empowerment serves as the central variable for economic resilience and cultural preservation. The study concludes that halal tourism must transcend marketing gimmicks to become a vehicle for human welfare (maqasid al-shariah), ensuring ecological, social, and economic sustainability through active community participation.